Intermediate algebra and trigonometry - Kuczynska, Anna; Larsen, Judy; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2019)
"This textbook is intended for adult learners who wish to review and improve their algebra skills. The content covers all the ABE outcomes for the Algebraic Math - Advanced Level. The concepts are explained concisely, but with enough depth to provide students with the background necessary for success in college or university level mathematics. The ample number of examples and exercises makes this text a great resource for students as well as for instructors"--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from PDF title page (viewed on January 16, 2020).
Keywords: Algebra -- Textbooks; Trigonometry -- Textbooks; Electronic books